Cadre-Led Sanitation Counseling and Maternal Stunting-Prevention Practices in Sigi Regency, Indonesia: A Cross-Sectional Study - Dedi Mahyudin Syam; Andi Bungawati; Udin Udin (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Stunting remains a major public health problem in Indonesia, particularly in high-burden areas such as Sigi Regency, Central Sulawesi. Poor sanitation and hygiene practices contribute to environmental enteric dysfunction (EED), which may impair nutrient absorption and child growth. Indonesia’s Community-Based Total Sanitation (STBM) program promotes sanitation-related behavior change through cadre-led interventions across five sanitation pillars. Methods: A cross-sectional design was used involving 80 mothers of stunted children under two years old, selected through proportional stratified random sampling across high-burden villages. Data were collected using a structured and validated 25-item questionnaire measuring behaviors aligned with the five STBM pillars. A score of ?75 (?75% of the maximum score) was categorized as "adequate," while a score <75 was classified as "inadequate." analysis was performed using Chi-square was conducted to determine associations between exposure to cadre-led activities and maternal sanitation and hygiene practices, with particular attention to behaviors.followed by logistic regression analysis. Results: Bivariate analysis showed significant associations between maternal stunting-prevention practices and counseling on open defecation elimination (p<0.00), handwashing with soap (p<0.001), and water and food management (p=0.001). However, multivariate analysis revealed that only handwashing-with-soap counseling remained significantly associated with good maternal stunting-prevention practices (Adjusted OR = 63.00; 95% CI for OR: 15.61–254.12; p<0.001). Conclusion: Handwashing-with-soap counseling was the strongest predictor of maternal stunting-prevention practices. These findings suggest that hygiene-focused behavioral interventions targeting fecal–oral transmission pathways may play a critical role in reducing stunting risk. Strengthening cadre-based handwashing promotion should be prioritized in community-based stunting prevention strategies.